STATUS AND PROBLEMS OF OILSEED PRODUCTION IN POLTAVA REGION - Єщенко, І. В. (Scientific Progress & Innovations, 2014)
Sufficiently rapid development of the oilseeds production industry and the increasing demand for vegetable fats in the world resulted a significant increasing of the scientific interest to problems ofoilseed production in Ukraine. The article discusses the major trends of this industry development, the external and internal factors which make an influence on it, organizational and economic peculiarities of the effective development of oilseed production industry, the analysis of economic efficiency ofoilseeds production has been provided, as well as the main reserves of its increase in Poltava regionhas been identified.